Otworzyć drzwi dla wszystkich... Solidarność z ubogimi, prawo do edukacji i uczelnie katolickie w społeczeństwie amerykańskim i polskim - BEYER, Gerald J.; CHABRAJSKA, Dorota (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Catholic social teaching posits the right to education of all people, including the poor. However, it is not exactly clear as to whether this includes access to higher education as a right. This article argues that Catholic social teaching’s understanding of the right to education must include access to higher education, especially for the economically marginalized, in knowledge−based societies such as the United States and Poland. Moreover, this article maintains that Roman Catholic colleges and universities must do all that they can to recruit, admit, and retain students from economically disadvantaged backgrounds in order to fulfill Catholic teaching on solidarity with the marginalized and the preferential option for the poor. First, the article discusses the right to education in international agreements and Catholic social teaching, highlighting Catholic social teaching’s emphasis on the importance of education in overcoming poverty and fostering the right to participation in the life of society. Relying on interdisciplinary perspectives, it also argues that in the United States and Poland the right to education must include access to higher education, particularly for the economically marginalized, who have become increasingly excluded from it. The second part of the article presents empirical data concerning the socioeconomic background of students from selected Catholic colleges and universities in the U.S. and Poland. This data reveals that many Catholic institutions of higher learning have not had great success in providing access to education to students of lesser means, while others have done a better job of fulfilling this aspect of their mission as Catholic colleges and universities. In conclusion, the article suggests how Catholic institutions might be able to progressively achieve this goal to a greater degree. Significant portions of this article appeared as a lengthier report. The author thanks The Program for Research on Religion and Urban Civil Society at The University of Pennsylvania for a grant that funded this research report and for permission Abstracts 356 to reprint it. I am also grateful for permission to reprint significant portions of Gerald J. Beyer, “Catholic Universities, Solidarity, and the Right to Education in the American Context,” Journal of Catholic Social Thought Vol. 7, No. 1 (Winter 2010): 145−79. Portions of this article will also appear in Gerald J. Beyer, “U.S. Catholic Higher Education: An Option for the Poor?,” U.S. Catholic